2006
DOI: 10.2353/ajpath.2006.060552
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of Multiple Genes in Gastric Glands with Intestinal Metaplasia

Abstract: Gene silencing by methylation of promoter CpG islands is deeply involved in cancers, but its involvement in polyclonal disorders is still unclear. Here, we analyzed the presence of gene silencing in intestinal metaplasia (IM) of the stomach, a polyclonal disorder, in which multiple gastric glands aberrantly differentiate into those with intestinal characteristics. By a genome-wide screening, CpG islands in the putative promoter regions of four genes (ZIK1, ZNF141, KAL1, and FGF14) were found to be specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…After identification of tumors in the endoscopic mucosal biopsy samples through light microscopy, tumor lesions were manually dissected and the dissected tissues were pooled together in a microtube containing lysis buffer and proteinase K. Whole tissue sections were used for DNA extraction of the chronic gastritis group samples. Chronic gastritis cases showing intestinal metaplasia were excluded from the present study because intestinal metaplasia itself is associated with increased DNA hypermethylation of CpG island loci [25] and our preliminary study confirmed this finding. Sodium bisulfite conversion of genomic DNA was performed as described [26].…”
Section: Dna Isolation and Bisulfite Modificationsupporting
confidence: 76%
“…After identification of tumors in the endoscopic mucosal biopsy samples through light microscopy, tumor lesions were manually dissected and the dissected tissues were pooled together in a microtube containing lysis buffer and proteinase K. Whole tissue sections were used for DNA extraction of the chronic gastritis group samples. Chronic gastritis cases showing intestinal metaplasia were excluded from the present study because intestinal metaplasia itself is associated with increased DNA hypermethylation of CpG island loci [25] and our preliminary study confirmed this finding. Sodium bisulfite conversion of genomic DNA was performed as described [26].…”
Section: Dna Isolation and Bisulfite Modificationsupporting
confidence: 76%
“…Because previous studies [18,26] revealed that intestinal metaplasia is accompanied by enhanced promoter CGI hypermethylation compared with chronic gastritis without intestinal metaplasia and our preliminary study revealed enhanced CGI hypermethylation in intestinal metaplasia regardless of H. pylori infection, cases that showed intestinal metaplasia or epithelial neoplasia in any of the four tissue samples were excluded from the study in order to focus on the effect of H. pylori infection on DNA methylation changes in chronic gastritis. Gastric carcinoma cases or chronic gastritis cases without intestinal metaplasia were included in the study.…”
Section: Dna Extraction and Bisulfite Modificationmentioning
confidence: 99%
“…In addition to the nine contiguous zinc fingers in the C-terminus, ZIK1 contains a KRAB-A domain thought to be involved in transcriptional repression. ZIK1 demonstrated aberrant DNA methylation, it might function on tumor development (39). It was unknown whether there was a relationship between decreasing VEGI174 expression level and increasing MYC or ZIK1 expression levels in RCC tissues.…”
Section: Discussionmentioning
confidence: 99%